Determinant Factors for Selecting the Contraceptive Acceptor Method in the Banjardowo Family Planning Village Semarang - Ratnawati, -; Sembodo, Tjatur; Masyhudi, - (Bangladesh Journal of Medical Science, 2021)
Objective: Indonesia’s population is ranked fourth in the world, while central Java is ranked third nationally. Governments are making efforts to control the population through familyplanning programs. The family planning program to increase the amount of coverage of longterm contraception methods (MKJP) is still low. The purpose of this study is to know the determinant factor associated with the selection of acceptor contraceptive methods. Materials and Methods: This method uses a cross-sectional approach conducted in a banjardowo semarang village with 103 samples. The inclusion criteria of a sample of women of childbearing age, having a husband, using contraception. The sampling technique used is simple random sampling. Data were analyzed with Chi Square and Fisher Exact Test. Results and Discussion: The results of data analysis have a significant relationship between the determinant factors with the choice of contraceptive methods, age (p = 0,000; PR = 2,273; CI = 1,184-4,364), the purpose of using contraception (p = 0.04; PR = 1.515; CI = 1.065-2.157 ), Current number of children (p = 0.02; PR = 1.767; CI = 1.075-2.904), people suggesting (p = 0.011; PR = 1.359; CI = 1.359 (1.083-1.705) and previous experience using contraception (p = 0,000; PR = 2, 067; CI = 1,416-3,018) There was no significant relationship on the Education factor (p = 0.754; PR = 0.895; CI = 0.673-1.190), employment (p = 0.274; PR = 1.148 ; CI = 0.885- 1.490), First pregnancy age (p =0.753; PR = 0.953; CI = 0.695-1.305), expected number of children (p = 0.667; PR = 1.054; CI = 0.833-1.333). Conclusions: determinant factors which shows a significant relationship in determining MKJP or non MKJP contraceptive methods are age, the purpose of using contraception, the number of children desired, the person suggesting and experience using previous contraceptives. mother’s education, mother’s occupation, age of first pregnancy and the number of children expected to be unrelated to the contraceptive method chosen by the acceptor. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.313-317